Réponses

2013-11-03T15:28:57+01:00
a) 7/3 ( 6x + 3 ) + 5/2 ( 4 - 2x )
= 7/3 * 6x + 7/3 * 3 + 5/2 * 4 + 5/2 * (-2x) 
= 14x + 7 + 10 - 5x
= 9x + 17

b) 4( 1 - 7y ) + ( 4y - 5 ) ( y - 1 )
= 4 * 1 + 4 * (-7y) + 4y * y + 4y * (-1) - 5 * y - 5 * (-1)
= 4 - 28y + 4y^2 - 4y - 5y + 5
= 9 + 4y^2 - 37y

c) 3t ( t + 1 ) + ( 5 + t ) ( t - 2 )
= 3t * t + 3t * 1 + 5 * t + 5 * (-2) + t * t + t * (-2)
= 3t^2 + 3t + 5t - 10 + t^2 - 2t
= 4t^2 + 6t - 10

d) ( 4k - 1 ) ( 9 + k ) - 9k ( 10 - 3k )
= 4k * 9 + 4k * k - 1 * 9 - 1 * k - 9k * 10 - 9k * (-3k)
= 36k + 4k^2 - 9 - 1k - 90k + 27k^2
= -55k + 31k^2 - 9

e) ( m + 2 ) ( 8 + 3m ) - 2 ( 1 - m ) ( m - 7 )
= m * 8 + m * 3m + 2 * 8 + 2 * 3m - 2 * 1 - 2 * (-m) - 2 * m - 2 * (-7)
= 8m + 3m^2 + 16 + 6m - 2 + 2m - 2m + 14
= 3m^2 + 14m + 30